Caloric restriction and heart function: is there a sensible link? - Han Xuefeng; Ren Jun (Acta Pharmacologica Sinica, 2016)
Calorie restriction (CR) is defined as a reduction in calorie intake below the usual ad libitum intake without malnutrition. Ample of clinical and experimental evidence has demonstrated that CR is capable of retarding aging process and development of cardiovascular disease. Although suppression of reactive oxygen species production and inflammation plays a central role in the favorable cardiovascular effects of CR, the health benefit of CR is believed to be ultimately mediated through a cadre of biochemical and cellular adaptations including redox homeostasis, mitochondrial function, inflammation, apoptosis and autophagy. Despite the apparent beneficial cardiovascular effects of CR, implementation of CR in the health care management is still hampered by apparent applicability issues and health concerns. Here we briefly review the cardiac consequence of CR and discuss whether CR may represent a safe and effective strategy in the management of cardiovascular health.